Improving Students’ Writing Skill in Writing Narrative Text Through Picture And Picture Method - M. Hilmy Hidayatullah (JOEY: Journal of English Ibrahimy, 2022)
One of the important materials in reading skills is narrative text. The narrative text is taught since the 8th grade of Junior High School and is a mandatory material until it is included in the National Examination (UN) grid, college entrance exams, and TOEFL. The narrative text is a type of English text that aims to tell a story that has a series of connected chronological events. It is the main part of English text taught in Junior High School. Unfortunately, researchers still found many students who did not master narrative texts, especially in grade 8 of SMP Ibrahimy 1 Sukorejo. The picture and picture model is one of the learning models that can improve students' writing skills in narrative texts. The Picture and Picture model has the same principle and way of working as the method of learning to compose pictures. Students are equally asked to arrange pictures that have been prepared sequentially and systematically. Systematic and sequential according to the reasoning and logical strength of students. This research used the classroom action research method and was conducted in 2 cycles through four stages, namely planning, implementation, observation, and reflection. Data collection techniques used were observation, questionnaires, and tests. The finding of this research showed that picture and picture models could improve students’ writing skills in writing narrative text.